2016
DOI: 10.1038/srep28957
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of EMG-torque relation in chronic stroke using linear electrode array EMG recordings

Abstract: The objective was to re-evaluate the controversial reports of EMG-torque relation between impaired and non-impaired sides using linear electrode array EMG recordings. Ten subjects with chronic stroke performed a series of submaximal isometric elbow flexion tasks. A 20-channel linear array was used to record surface EMG of the biceps brachii muscles from both impaired and non-impaired sides. M-wave recordings for bilateral biceps brachii muscles were also made. Distribution of the slope of the EMG-torque relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…Although the ANOVA did not report significant main effect of the model on the R-square, the exponential model truly outperformed the linear model in characterizing EMG RMS-torque relation, with statistical significance reported by the pairwise comparisons. This confirmed previous finding that the EMG RMS amplitude of the BB muscle increased faster with the increment of muscle force, and represented a nonlinear EMG RMS-torque relation [8,[15][16][17].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although the ANOVA did not report significant main effect of the model on the R-square, the exponential model truly outperformed the linear model in characterizing EMG RMS-torque relation, with statistical significance reported by the pairwise comparisons. This confirmed previous finding that the EMG RMS amplitude of the BB muscle increased faster with the increment of muscle force, and represented a nonlinear EMG RMS-torque relation [8,[15][16][17].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the relation between EMG and muscle contraction level (described as force or torque alternatively) offers a useful tool for examining muscle functions and deficits, with wide biomedical and biomechanical applications [3,[5][6][7]. Among them, the EMG signals were usually analyzed with time-domain amplitude-associated and frequency-domain parameters including root mean square (RMS), averaged rectified value (ARV), median frequency (MDF) and mean power frequency (MPF) of EMG signal [8][9][10][11][12][13][14][15][16][17]. Sbriccoli et al [8] reported that the RMS of the Subjects completed a series of isometric elbow flexion tasks while the forearm of the dominant side was positioned on an equipment with the elbow joint at 90 • , the shoulder abducted at 45 • and flexed at approximately 30 • .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the reliance on biosignals, those systems are inoperable without sensors. Movement based on EMG data extraction from stroke patients is difficult because of abnormal EMG-torque relationship [13]. The adaptive control algorithm used in exoskeleton results in constant draining of energy for controlling the variable joint torque and active range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the issues such as cost, compatibility with user, efficiency, accuracy and acceptability restrict the use. Fine EMG signal extraction from stroke patients is troublesome due to irregular EMG-torque relations in stroke [4]. IMU and accelerometer are attached to the human body which restricts motion of the users and they feel captive wearing them [5].…”
Section: Introductionmentioning
confidence: 99%